Capture, analysis and measurement of images of speech and smile dynamics - Vera Lúcia Cosendey; Stephanie Drummond; Jonas Capelli Junior (Dental Press Editora, 2012)
INTRODUCTION: Dynamic analysis of smile and speech makes it easier to identify the features that define facial esthetics while allowing researchers to study different variables and observe the effects of aging. OBJECTIVE: The aim of this study is to present a method for capturing, analyzing and measuring video images to support the study of speech and smile dynamics. METHODS: Natural head positioning was standardized with the aid of a head holder (cephalostat). Image acquisition is performed with a video camera attached to a tripod, positioned at a fixed distance of 0.90 m. The subjects are trained to say out loud: "Tia Ema torcia pelo antigo time da Tchecoslováquia" and then to smile. The resulting images are fragmented and yielded four pictures that best represent a resting position, the least exposure of maxillary incisors, the greatest exposure of upper and lower incisors, and a posed smile. A freeware computer program called VIDEOMED was used to carry out measurements. CONCLUSION: The method presented in this study is an effective resource to record images captured during rest, speech and smile, thereby enabling a better understanding of changes in perioral soft tissues. INTRODUÇÃO: a análise dinâmica do sorriso e da fala facilita a identificação de características da estética facial, possibilita o estudo de diferentes variáveis e viabiliza a observação dos efeitos do envelhecimento. OBJETIVO: o objetivo desse trabalho é apresentar um método de captura, análise e medição de imagens por meio de vídeos, para o estudo da dinâmica da fala e do sorriso. MÉTODOS: foi padronizado o posicionamento da cabeça em posição natural com o auxílio de um cefalostato. A captura de imagens foi realizada por uma câmera de vídeo, acoplada a um tripé, posicionada a uma distância fixa de 0,90m. Os indivíduos foram treinados a pronunciar a frase "Tia Ema torcia pelo antigo time da Tchecoslováquia" e depois sorrir. As imagens geradas foram fragmentadas de forma a gerar quatro quadros que melhor representassem o repouso, a menor exposição de incisivo superior, a maior exposição de incisivos superior e inferior, e o sorriso posado. Para realização das medidas, utilizou-se um programa específico, chamado VideoMed. CONCLUSÃO: o método apresentado torna possível um registro eficaz para captura de imagens durante o repouso, a fala e o sorriso, possibilitando um maior entendimento sobre as alterações dos tecidos moles peribucais.